2014
DOI: 10.1093/brain/awu112
|View full text |Cite
|
Sign up to set email alerts
|

Feeling unreal: a functional imaging study in patients with Kleine-Levin syndrome

Abstract: Kleine-Levin syndrome is characterized by relapsing-remitting episodes of severe hypersomnia, cognitive impairment, apathy, derealization and behavioural disturbances. Between episodes, patients have normal sleep, mood and behaviour. Functional imaging studies performed in small series of patients with Kleine-Levin syndrome with visual or semi-quantitative, uncontrolled analysis yielded equivocal brain changes. Using whole brain voxel-based group analysis, we compared brain perfusion scintigraphy during and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
66
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 31 publications
2
66
0
3
Order By: Relevance
“…Our findings suggest that episodic hypothalamic dysfunction and state-dependent variations in hypocretin levels might occur in KLS, concurring with some functional neuroimaging findings [2,3,9,10]. Intermittent alteration of the diencephalic system may vary in degree between patients and between episodes, depending on the phenotype and its severity.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings suggest that episodic hypothalamic dysfunction and state-dependent variations in hypocretin levels might occur in KLS, concurring with some functional neuroimaging findings [2,3,9,10]. Intermittent alteration of the diencephalic system may vary in degree between patients and between episodes, depending on the phenotype and its severity.…”
Section: Discussionsupporting
confidence: 89%
“…This is supported by functional imaging studies during episodes, showing changes in activity in thalamic and hypothalamic regions, and in the frontal and temporal lobes [1,[3][4][5]. Analysis of case reports suggest that KLS has a genetic component [1,[6][7][8].…”
Section: Introductionmentioning
confidence: 73%
“…Mixed evidence suggests hypothalamic dysfunction in KLS (Koerber et al 1984;Gadoth et al 1987;Fernábdez et al 1990;Chesson et al 1991;Malhotra et al 1997;Mayer et al 1998;Kas et al 2014). Evidence for thalamic involvement also exists; Tc-99m ethyl cysteinate dimer (ECD) single-photon emission CT analysis during symptomatic periods of KLS has demonstrated thalamic hypoperfusion (Huang et al 2005;Hong et al 2006;Huang et al 2012b;Kas et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for thalamic involvement also exists; Tc-99m ethyl cysteinate dimer (ECD) single-photon emission CT analysis during symptomatic periods of KLS has demonstrated thalamic hypoperfusion (Huang et al 2005;Hong et al 2006;Huang et al 2012b;Kas et al 2014). MRI assessment of PANDAS youth has demonstrated enlarged basal ganglia (Giedd et al 1996(Giedd et al , 2000, and positron emission tomography has demonstrated increased activated microglial cells, which are suggestive of neuroinflammation, in bilateral caudate nuclei and bilateral lentiform in youth with PANDAS (Kumar et al 2014).…”
Section: Discussionmentioning
confidence: 99%